ANALISIS BRAND SWITCHING AQUA KE LE MINERALE OLEH GEN Z KOTA PEKANBARU - Alvi, Alvi; Lathif Arafat; Kanzi Mahardiga Labaga; Irsan Ali nasution; Lola Maharani (JEBIM Prima, 2026)
This study examines brand switching behavior from Aqua to Le Minerale among Generation Z consumers in Pekanbaru. While Aqua has traditionally dominated Indonesia’s bottled water market, its market share has shown a declining trend since 2015. In contrast, Le Minerale, introduced in 2016, has demonstrated consistent growth. Using a quantitative approach, data were collected from 53 respondents and analyzed with SmartPLS to assess both inner and outer model validity. The results show that social media advertising has a positive and significant effect on brand switching (p = 0.06 < 0.05; t = 2.740 > 1.674) and on variety seeking (p = 0.001 < 0.05; t = 3.193 > 1.674). Furthermore, variety seeking significantly influences brand switching (p = 0.000 < 0.05; t = 7.327 > 1.674). The mediating effect was also confirmed, as social media advertising indirectly affects brand switching through variety seeking (p = 0.06 < 0.05; t = 1.740 > 1.674). In contrast, price perception shows no significant effect on either brand switching or variety seeking, and variety seeking does not mediate the relationship between price perception and brand switching. These findings highlight that social media advertising and variety seeking are key determinants of brand switching behavior among Generation Z, while price perception plays a negligible role in this context.